URGENCY OF MARRIAGE REGULATION BETWEEN CIVIL STATE EMPLOYEES AND FOREIGN CITIZENS - Dewi Masyitha (Lambung Mangkurat Law Journal, 2021)
Mixed marriage has become a common thing nowadays, but the arrangement in Indonesia is still limited. Even until now there has been no regulation regarding mixed marriages between Civil Servants and Foreign Citizens, even though their status as Civil Servants has various special consequences. Thus, there is a need for a special arrangement to accommodate the rights and obligations of perpetrators of mixed marriages between civil servants and foreign citizens. This type of research uses a normative juridical approach. Based on this research, it can be concluded that the urgency of establishing a regulation on mixed marriage between civil servants and foreigners is needed as a guide for civil servants in fulfilling their rights and obligations and their implementation needs to be outlined in the revision of PP. 10 of 1983 and PP. 7 of 1977.